2014
DOI: 10.2478/s11535-014-0331-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of chronic low-dose effects of alpha- and beta-emitting radionuclides on marine bacteria

Abstract: Effects of Americium-241 (241Am), alpha-emitting radionuclide of high specific radioactivity, and tritium (3H), beta-emitting radionuclide, on luminous bacteria Photobacterium phosphoreum were compared. Bioluminescence intensity served as a marker of bacterial physiological activity. Three successive stages in the bioluminescence response to 241Am and 3H were found under conditions of lowdose irradiation: (1) absence of effects, (2) activation, and (3) inhibition. They were interpreted in terms of bacterial re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 32 publications
2
31
0
Order By: Relevance
“…As follows from the previous section, luminous bacteria revealed complex responses to chronic effect of Am-241 and H-3 (Rozhko et al, 2007;Alexandrova et al, 2011;Selivanova et al, 2013Selivanova et al, , 2014Kudryasheva et al, 2014) (Figs. 1e3) in the range of radioactivities 1.0e6.7 kBq/L and 0.0002e200 MBq/L, respectively.…”
Section: On Molecular Mechanisms Of Radiation Hormesis and Toxicitymentioning
confidence: 52%
See 1 more Smart Citation
“…As follows from the previous section, luminous bacteria revealed complex responses to chronic effect of Am-241 and H-3 (Rozhko et al, 2007;Alexandrova et al, 2011;Selivanova et al, 2013Selivanova et al, , 2014Kudryasheva et al, 2014) (Figs. 1e3) in the range of radioactivities 1.0e6.7 kBq/L and 0.0002e200 MBq/L, respectively.…”
Section: On Molecular Mechanisms Of Radiation Hormesis and Toxicitymentioning
confidence: 52%
“…Effects of alpha-and beta-emitting radionuclides (Am-241, U-(235þ238), and H-3) on luminous marine bacteria Photobacterium phosphoreum were reported in a series of works (Rozhko et al, 2007(Rozhko et al, , 2008Alexandrova et al, 2010Alexandrova et al, , 2011Selivanova et al, 2013Selivanova et al, , 2014. The detailed investigation of the effects was conducted using tritium and Am-241 as examples.…”
Section: Effects Of Alpha-and Beta-emitting Radionuclides On Luminousmentioning
confidence: 99%
“…Min et al showed that DNA damage in bacterial cells was positively correlated with the dose of gamma radiation [15]. On the contrast, a few scientific researches proposed that the low-dose of radiation gave the stimulatory effect, increasing function and resistance of the cellular organism [16,17]. However, to date, this phenomenon has been controversy [18].…”
Section: Introductionmentioning
confidence: 99%
“…Three successive stages in bioluminescence response to ionizing radiation were demonstrated: (1) absence of effect (stress recognition), (2) activation (adaptive response), and (3) inhibition (suppression of the physiological function or radiation toxicity). The effects of alpha and beta emitting radionuclides were compared in (Selivanova et al, 2014); different effects were explained with the differences in the Reactive Oxygen Species (ROS) concentration and the efficiency of biochemical redox processes (Alexandrova et al, 2011;Selivanova et al, 2013). Low-dose effects of gamma radiation on luminous bacteria were studied in (Kudryasheva et al, 2017).…”
Section: Introductionmentioning
confidence: 99%